Antioxidant Power on Dermal Cells by Textiles Dyed with an Onion (Allium cepa L.) Skin Extract - Claudia Volpi; Desirée Bartolini; Virginia Brighenti; Francesco Galli; Matteo Tiecco; Federica Pellati; Catia Clementi; Roccaldo Sardella (MDPI AG, 2021)
In this study, the phenol loading and antioxidant activity of wool yarn prepared with the aqueous extract of onion (Allium cepa L.) skin was enhanced by implementing the dyeing process with the use of alum as a mordant. Spectrophotometric and chromatographic methods were applied for the characterization of polyphenolic substances loaded on the wool yarn. The antioxidant/anti-inflammatory properties were evaluated by determining the level of intra- and extra-cellular reactive oxygen species (ROS) production in keratinocytes and dermal fibroblasts pre-treated with lipopolysaccharide put in contact with artificial sweat. An elevated dye uptake on wool was observed for the pre-mordanted sample, as demonstrated by high absorbance values in the UV-Visible spectral range. Chromatographic results showed that protocatechuic acid and its glucoside were the main phenolic acid released in artificial sweat by the wool yarns, while quercetin-4'-glucoside and its aglycone quercetin were more retained. The extract released from the textile immersed in artificial sweat showed a significant reducing effect on the intra-and extracellular ROS levels in the two cell lines considered. Cytofluorimetric analyses demonstrated that the selected mordant was safe at the concentration used in the dyeing procedure. Therefore, alum pre-mordanted textiles dyed with onion-skin extracts may represent an interesting tool against skin diseases.